METABOLIC SYNDROME IN YOUNG RHEUMATOID ARTHRITIS PATIENTS - Shaikh, Sana; Dahani, Assadullah; Arain, Shafique Rehman; Khan, Furqan (Journal of Ayub Medical College Abbottabad, 2020)
Background: Metabolic Syndrome is strongly associated with Rheumatoid Arthritis, which significantly increases cardiovascular complications and hence morbidity and mortality. Treating Metabolic Syndrome decreases cardiovascular related disease flares and deaths. This study evaluates prevalence of metabolic syndrome in young Rheumatoid Arthritis patients. Methods: This Cross-sectional study was conducted in rheumatology department of a tertiary care hospital in Karachi. All diagnosed cases of rheumatoid arthritis from April to August 2018 were consecutively included. Disease activity of rheumatoid arthritis assessed by Clinical Disease Activity Index (CDAI). Associate determinants of rheumatoid arthritis were measured along with outcome variables. Results: Out of 104 rheumatoid arthritis patients, 34 (32.7%) found to have metabolic syndrome in whom 20 (58.8%) of patients were seropositive. A significant association of metabolic syndrome was found with age (p-value 0.023), BMI (p-value 0.006), waist circumference (p-value 0.002), FBS (p-value <0.001), SBP (p-value <0.001), DBP (p-value <0.001), TG (p-value <0.001), HDL (p-value 0.022), and Methotrexate drug history (p-value 0.030). Conclusion: We conclude that metabolic syndrome is highly prevalent in young rheumatoid patients with rheumatoid arthritis. Treating Metabolic Syndrome decreases cardiovascular related disease flares and deaths. This young population base study will help out to estimate the exact burden of Metabolic Syndrome to decrease overall morbidity and mortality. Keywords: Rheumatoid Arthritis; Metabolic Syndrome; Cardiovascular disease